R&D investment in new product development within the technology sector - Almeida, João Tiago Coelho de (2015)
Through the fast growing globalization, the consumption of technology is showing a massive increase year after year. Since the beginning of this millennium, the number of people using all kinds of technology products is being spreading through all around the world. The consumers unsustainable needs for new and better technology products are the reason to the product life cycle decrease. In order to have a competitive product, companies have to focus their resources to new product development process by investing in research and development. This dissertation was made with the purpose to understand the technology companies growth when investing in research and development. There are different technology sectors where the companies growth effects are different when they invest in research and development. Also, depending on the companies profitability, the research and development investment may have more or less effect in their growth. Consequently, the propose of this dissertation is to understand how the research and development investment has effect in the technology companies growth. In order to accomplish equitable results, we analyzed a few financial variables such as the asset growth, the return on assets and the return on equity. To achieve accomplish the study results, it was conducted a linear regression model and a quantile regression model to analyze the variables relations. This study shows which type of companies can accomplish higher results when investing in research and development. It also estimate a general positive effect from the research and development investment.